2011
DOI: 10.1089/bfm.2010.0018
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Initiation and Exclusivity of Breastfeeding in Al Hassa, Saudi Arabia

Abstract: The rate of initiation and exclusivity of breastfeeding in Al Hassa is far below the World Health Organization recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
128
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(163 citation statements)
references
References 25 publications
24
128
9
1
Order By: Relevance
“…This could be because of the fact that primipara mothers might be young people who could have better access to media and be more knowledgeable on advantage of exclusive breast feeding. The finding was in agreement to a study done in peninsular Malaysia [13] but was not consistent to studies done in Saudi Arabia, Canada, West India, and in the Thane district of India where multiparous mother were more likely to exclusively breastfeed than primipara mothers [8,23,24,27].…”
Section: Determinants Of Ebfsupporting
confidence: 72%
See 1 more Smart Citation
“…This could be because of the fact that primipara mothers might be young people who could have better access to media and be more knowledgeable on advantage of exclusive breast feeding. The finding was in agreement to a study done in peninsular Malaysia [13] but was not consistent to studies done in Saudi Arabia, Canada, West India, and in the Thane district of India where multiparous mother were more likely to exclusively breastfeed than primipara mothers [8,23,24,27].…”
Section: Determinants Of Ebfsupporting
confidence: 72%
“…The sample size was calculated using single population proportion formula by considering the following assumptions: a 95% confidence level, 5% margin of error, 12% proportion of exclusive breastfeeding practice [8] …”
Section: Sample Size Determination and Sampling Proceduresmentioning
confidence: 99%
“…In the present study, only 12.8% started within the first hour. Nearly similar rates of initiation within one hour (11.4% -13.2%) were reported in other regions of KSA by El-Gilany et al and Amin et al (33,34). Higher rates of commencing breastfeeding, within the first hour after delivery, were also reported as follows: 23.2% in Jeddah (25); 31% in Abha (7); 39.0% in Kuwait (35); 18.3% in Lebanon (36); 43.7-45.5% in Turkey (6, 37); and 49.5% in Jordan (38).…”
Section: Discussion:-supporting
confidence: 85%
“…Other support study findings reported by (Singh, 2012) that (74%) of mothers initiated breast feeding within 6 hours. On the other hand (El-Gilany etal, 2011) reported that only (11.4%) of mothers started breastfeeding within the first hour after delivery, while (Amin & Hablas, 2011) found that (77.8%) of studied mothers had initiated breastfeeding within 24 hours post-partum.…”
Section: Discussionmentioning
confidence: 96%